Hepatic rhythmicity of endoplasmic reticulum stress is disrupted in perinatal and adult mice models of high-fat diet-induced obesity. (19th May 2017) - Soeda, Junpei; Cordero, Paul; Li, Jiawei; Mouralidarane, Angelina; Asilmaz, Esra; Ray, Shuvra; Nguyen, Vi; Carter, Rebeca; Novelli, Marco; Vinciguerra, Manlio; Poston, Lucilla; Taylor, Paul D.; et al.
Abstract: We investigated the regulation of hepatic ER stress in healthy liver and adult or perinatally programmed diet-induced non-alcoholic fatty liver disease (NAFLD). Female mice were fed either obesogenic or control diet before mating, during pregnancy and lactation. Post-weaning, offspring from each maternal group were divided into either obesogenic or control diet. At six months, offspring were sacrificed at 4-h intervals over 24 h. Offspring fed obesogenic diets developed NAFLD phenotype, and the combination of maternal and offspring obesogenic diets exacerbated this phenotype. UPR signalling pathways (IREα, PERK, ATF6) and their downstream regulators showed different basal rhythmicity, which was modified in offspring exposed to obesogenic diet and maternal programming. The double obesogenic hit increased liver apoptosis measured by TUNEL staining, active caspase-3 and phospho-JNK and GRP78 promoter methylation levels. This study demonstrates that hepatic UPR is rhythmically activated. The combination of maternal obesity (MO) and obesogenic diets in offspring triggered altered UPR rhythmicity, DNA methylation and cellular apoptosis.